Mechanical and electrical equipment for buildings - Stein, Benjamin; Reynolds, John S. (New York : Wiley, 1992)
This edition extends the philosophy of the seventh edition, emphasizing the themes of energy coservation and the use of renewable energy while keeping the reader informed of the major changes in equipment technology wrought by the microprocessor and the computer.
Contents: Energy overview-- thermal control-- water and waste-- fire protection-- electricity-- ilumination-- signal equipment-- transportation-- acoustics-- appendices--
Includes index.
Keywords: BUILDINGS -- MECHANICAL EQUIPMENT